Differential characteristics of photochemical acclimation to cold in two contrasting sweet sorghum hybrids - Zegada Lizarazu, Walter; Luna, Dario Fernando; Monti, Andrea (Wiley; Scandinavian Plant Physiology Society, 2019)
Sweet sorghum has a photosynthetic system which is highly sensitive to cold stress and hence strongly limits its development in temperate environments; therefore, the identification of key exploitable cold tolerance traits is imperative. From a preliminary field trial, two dissimilar sweet sorghum hybrids (ICSSH31 and Bulldozer), in terms of early vigor and productivity, were selected for a controlled‐environment trial aiming at identifying useful traits related to acclimation mechanisms to cold stress. The higher cold tolerance of Bulldozer was partially related to a more efficient photochemical regulation mechanism of the incoming light energy: the higher tolerance of photosystem II (PSII) to photo‐inactivation was because of a more effective dissipation capacity of the excess of energy and to a more balanced diversion of the absorbed energy into alternative energy sinks. ICSSH31 increased the dissipation and accumulation of a large amount of xanthophylls, as in Bulldozer, but, at the same time, inactivated the oxygen evolving complex and the re‐synthesis of chlorophyll (Chl) a and b, thus, leading to an overproduction of CO2 fixation enzymes after re‐warming. In summary, in Bulldozer, the acclimation adjustments of the photosynthetic apparatus occurred through an efficient control of energy transfer toward the reaction centers, and this likely allowed a more successful seedling establishment; ICSSH31, conversely, exhibited a fast re‐synthesis of Chl pigments, which appears to divert photosynthates from dry matter accumulation. Such broad acclimation traits may constitute a source for selecting higher genetic gain traits relevant for enlarging the growing season of promising biomass sorghum ideotypes in temperate climates.